THE INFLUENCE OF BK TEACHERS' UNDERSTANDING OF PROFESSIONAL ETHICS AND COMPETENCE ON THE QUALITY OF GUIDANCE AND COUNSELING SERVICES - Shivani Bella Fitriani; Dodi Suryana; Ahman Ahman (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
This study aims to show the influence of BK teachers' understanding of professional ethics and competence on the quality of guidance and counseling services. This research uses a literature review approach obtained by the source through the data base of national and international journal providers found on the google scholar page which is then analyzed. The results of this study concluded that understanding ethics and fulfilling the competence of BK teachers affects the guidance and counseling services provided. Because guidance and counseling services cannot be provided with just anyone, to facilitate the guidance and counseling process, BK teachers must have competencies and realize the code of ethics in order to achieve effective goals that are accountable to clients.